Insights into binding molecular mechanism of hemagglutinin H3N2 of influenza virus complexed with arbidol and its derivative: A molecular dynamics simulation perspective. (December 2022) - Boonma, Thitiya; Soikudrua, Nattharuja; Nutho, Bodee; Rungrotmongkol, Thanyada; Nunthaboot, Nadtanet
Abstract: Recently, the H3N2 influenza outbreak has caused serious global public health concern for future control of the next influenza pandemic. Since using current anti-influenza drugs targeting neuraminidase (oseltamivir and zanamivir) and the proton M2 channel (amantadine and rimantadine) leads to drug resistance, it is essential to seek new anti-viral agents that act on additional viral targets. Hemagglutinin (HA), a glycoprotein embedded in the viral surface and playing a critical role in influenza the viral replication cycle has become an attractive target. This work investigates the molecular binding mechanism of HA H3N2 of influenza virus complexed with the fusion inhibitor, arbidol and its derivative (der-arbidol), by means of molecular dynamics simulation. The result showed that the arbidol derivative could form many and strong hydrogen bonds with the HA surrounding amino acids comprising GLU1032 ( 1 ), LYS3071 ( 1 ) and LYS3102 ( 1 ) while arbidol makes this type of interaction with only LYS582 ( 1 ). The introduction of hydroxyl group at the meta-position of the thiophenol ring was detected to replace the nearby water molecule, thus allowing the direct hydrogen bond formation between der-arbidol and GLU1032 ( 1 ) of HA residue. Furthermore, the salt bridge networks established among residues GLU572 ( 1 )···ARG542 ( 1 )···GLU972 ( 2 ) were considerably more stable in HA-Der-arbidol than that found in HA-Arbidol. The predicted protein-ligand binding free energies were in agreement with experimental data indicating that der-arbidol exhibits higher inhibitory potency against HA H3N2 of influenza virus. Detailed information could be useful for further designing and optimizing HA fusion inhibitors with improved efficiency. Graphical Abstract: ga1 Highlights: MD simulations of HA inhibitors (arbidol and its derivative) complexed with HA H3N2 of influenza virus were carried out. Der-arbidol formed many and strong H-bonds with HA residues (GLU1032 ( 1 ), LYS3071 ( 1 ) and LYS3102 ( 1 )) than that of arbidol. Addition of OH at the meta-position of thiophenol ring in der-arbidol was found to replace the nearby water molecules. Salt bridge networks formed by GLU572 ( 1 )··ARG542 ( 1 )··GLU972 ( 2 ) were more stable in HA-Der-arbidol than that of HA-Arbidol. Binding free energy calculations supported the high inhibitory potency of der-arbidol against HA H3N2 of influenza virus.